Energy Access and Productive Uses for the Urban Poor : Final Report on Ghana Scoping Study - The Energy and Resources Institute (World Bank, Washington, DC, 2014)
The aim of the scoping study was to gain an understanding of the productive activities slum dwellers engage in that rely on energy services and the potentials and challenges of slums in Ghana regarding access to modern energy services and income generation from productive activities. The objective of the ESMED-EAfUP (Energy Sector Management Assistance Program - ESMAP/SME Development - Energy Access for the Urban Poor) programme is 'to create and sustain a network of energy practitioners to support development of Micro, Small and Medium Enterprises (MSME) as users and providers of modern energy services for slum upgrading programs.'. Using ability to adopt safer and modern energy forms as a criterion in assessing the effective deployment of safer and modern energy forms, the study concluded that the high propensity to save is an opportunity for their deployment if they can be sensitized about the benefits of using modern energy forms, which many of the slum dwellers are not aware of. Most enterprise owners could also capitalize on the credit policies of the financial institutions they saved with to adopt the modern energy forms. Lack of education and limited awareness about the benefits of using clean, efficient and improved energy forms were some of the reasons for the use of inefficient and illegal energy forms among the slum dwellers. The study recommends awareness creation among the slum dwellers about the benefits of using legal, clean and efficient energy forms in productive enterprises, which the Non-Governmental Organizations (NGOs) can take up. A major benefit of this study which is worth mentioning is the learning and sharing that took place among the research team because apart from the findings of this study that unraveled some relevant information that many stakeholders working in the cities of Ghana did not know about slums, there was also a lot of sharing of experiences that took place.